Calcium: a central player in Cryptococcus biology. (June 2021) - Squizani, Eamim D.; Reuwsaat, Júlia C.V.; Motta, Heryk; Tavanti, Andrea; Kmetzsch, Livia
Abstract: Adaptation to the host environment is crucial for fungal pathogenesis. Calcium (Ca 2+ ) signals are essential for fungal cells to respond rapidly to stress stimuli. In eukaryotic cells, Ca 2+ is the main intracellular secondary messenger and regulates a myriad of processes, including the cellular fitness of the fungal pathogen Cryptococcus neoformans . In this minireview, we highlight the main cryptococcal processes regulated by Ca 2+ . Moreover, we underline all the characterized proteins responsible for intracellular calcium homeostasis in this yeast, such as Ca 2+ transporters and binding proteins. These elements, in general, are essential for C. neoformans' growth and adaptation to the host environment, as well as to virulence mechanisms. We also revisit the specific traits of the calcineurin signaling pathway in C. neoformans, which is the major pathway regulated by calcium and is crucial for yeast pathogenesis, adaptation, and growth at 37 °C. Notably, several Ca 2+ -related functions are highly conserved throughout fungal cells. Moreover, C. neoformans exhibits exclusive, significant features that are required for disease progression, thus attracting attention as feasible targets for antifungal drug development. Collectively, all the available data related to Ca 2+ processes clarify the complex role that Ca 2+ plays within cryptococcal cells, participating in host adaptation, transmigration, antifungal resistance, cell growth, and more.